2014
DOI: 10.1021/am5046185
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Opening Polymerization for Hyperbranched Polycationic Gene Delivery Vectors with Excellent Serum Tolerance

Abstract: In order to improve the transfection efficiency (TE) and biocompatibility, we synthesized a series of hyperbranched cationic polymers by ring-opening polymerization between diepoxide and several polyamines. These materials can condense plasmid DNA efficiently into nanoparticles that have much lower cytotoxicity than those derived from bPEI. In vitro transfection experiments showed that polymers prepared from branched or cyclic polyamine (P1 and P5) exhibited TE several times higher than 25KDa bPEI. More signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 53 publications
(90 reference statements)
0
40
0
Order By: Relevance
“…TEM and/or cryo-TEM studies have reported many micrographs to characterize the size, shape, and morphology of a wide variety of lipoplexes as: (a) pDNA with GCLs [45,54,57,62,64,75,93,115,117,118,120], MVCLs [63], cationic polymers [107,133,[169][170][171] or polycations [40,84,100,136]; and (b) siRNA with cationic polymers [90,104]. Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…TEM and/or cryo-TEM studies have reported many micrographs to characterize the size, shape, and morphology of a wide variety of lipoplexes as: (a) pDNA with GCLs [45,54,57,62,64,75,93,115,117,118,120], MVCLs [63], cationic polymers [107,133,[169][170][171] or polycations [40,84,100,136]; and (b) siRNA with cationic polymers [90,104]. Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…(ii) multivalent cationic lipids [67,78,139,178,181], derivated oligoamines [182] and tripeptide multivalent lipids [122]; (iii) cationic polymers derivatives from PEI [124,127,183,184], PAMAM [132,140], PDMAEMA [123,133,185], PAA [103,131,186,187], chitosan [188], polyphosphoramidates [189], polyhydroxyalkanoate [92], polyamines [107], polyaminoacids [127,190] or diblock copolymers [191]; (iv) polycations from calixarene [40,136,165,192] or cyclodextrin [134,135,142,164,193] derivatives; (v) lipopolymers from lysine derivatives [170]; (vi) pendant polymercationic cyclodextrins [129,130,163]; and (vii) cationic polymer-cyclodextrin polyrotaxanes [89]. The picture that results from these transfection studies is that many of the polyplexes show efficacies comparable to that reported by the Lipo2000 positive control and also by most of the commercial or synthezised univalent CLs, but its efficacy as transfecting agents of DNA is still below than that reported by most of t...…”
Section: Biochemistry Characterizationmentioning
confidence: 99%
See 3 more Smart Citations